Measurements of [Zeta]γ and [Zeta]γγ production in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physical review, 2016)
The production of Z bosons with one or two isolated high-energy photons is studied using pp collisions at √s=8 TeV. The analyses use a data sample with an integrated luminosity of 20.3 fb−1 collected by the ATLAS detector during the 2012 LHC data taking. The Zγ and Zγγ production cross sections are measured with leptonic (e+e−, μ+μ−, ν¯ν) decays of the Z boson, in extended fiducial regions defined in terms of the lepton and photon acceptance. They are then compared to cross-section predictions from the Standard Model, where the sources of the photons are radiation off initial-state quarks and radiative Z-boson decay to charged leptons, and from fragmentation of final-state quarks and gluons into photons. The yields of events with photon transverse energy ET>250 GeV from ℓ+ℓ−γ events and with ET>400 GeV from ν¯νγ events are used to search for anomalous triple gauge-boson couplings ZZγ and Zγγ. The yields of events with diphoton invariant mass mγγ>200 GeV from ℓ+ℓ−γγ events and with mγγ>300 GeV from ν¯νγγ events are used to search for anomalous quartic gauge-boson couplings ZZγγ and Zγγγ. No deviations from Standard Model predictions are observed and limits are placed on parameters used to describe anomalous triple and quartic gauge-boson couplings.